Effect of cooling rate after solution treatment on subsequent phase separation during aging of Fe-Cr alloys: A small-angle neutron scattering study. (1st August 2017) - Xu, Xin; Odqvist, Joakim; Colliander, Magnus Hörnqvist; King, Stephen; Thuvander, Mattias; Steuwer, Axel; Hedström, Peter
Abstract: The effect of cooling rate after solution treatment on the initial structure of concentrated binary Fe-Cr alloys and the effect of the initial structure on phase separation during subsequent aging has been investigated. The nano-scale compositional fluctuations in the bulk of the alloys are studied using small-angle neutron scattering and the results are compared with simulations using the Cahn-Hilliard-Cook (CHC) model. The alloys investigated represent different mechanisms of phase separation and at higher Cr content, when spinodal decomposition (SD) is favored, the initial Cr compositional fluctuations due to slow cooling after solution treatment reduce the kinetics of phase decomposition, whereas, at lower Cr composition when nucleation and growth is favored, the kinetics of phase decomposition is more rapid. Regardless of the nominal Cr composition of the alloy, the phase decomposition after extended aging up to 300 h at 748 K is always larger for the more non-random initial structure. The CHC modeling of the cooling process and subsequent initial aging (below 10 h) is in reasonable qualitative agreement with the experimental results for the Fe-40 wt.% Cr alloy decomposing via SD. However, the modeling approach must be refined for accurate quantitative modeling of the full SD process, including coarsening. Graphical abstract: